A Quasi-Experimental Evaluation of a Nutrition Behavior Change Intervention Delivered Through Women's Self-Help Groups in Rural India: Impacts on Maternal and Young Child Diets, Anthropometry, and Intermediate Outcomes. Issue 6 (11th April 2022) - Scott, Samuel; Gupta, Shivani; Menon, Purnima; Raghunathan, Kalyani; Thai, Giang; Quisumbing, Agnes; Prasad, Vandana; Hegde, Aditi; Choudhury, Avijit; Khetan, Madhu; Nichols, Carly; Kumar, Neha
ABSTRACT: Background: Women's self-help groups (SHGs) have become one of the largest institutional platforms serving the poor. Nutrition behavior change communication (BCC) interventions delivered through SHGs can improve maternal and child nutrition outcomes. Objectives: The objective was to understand the effects of a nutrition BCC intervention delivered through SHGs in rural India on intermediate outcomes and nutrition outcomes. Methods: We compared 16 matched blocks where communities were supported to form SHGs and improve livelihoods; 8 blocks received a 3-y nutrition intensive (NI) intervention with nutrition BCC, and agriculture- and rights-based information, facilitated by a trained female volunteer; another 8 blocks received standard activities (STD) to support savings/livelihoods. Repeated cross-sectional surveys of mother-child pairs were conducted in 2017–2018 ( n  = 1609 pairs) and 2019–2020 ( n  = 1841 pairs). We matched treatment groups over time and applied difference-in-difference regression models to estimate impacts on intermediate outcomes (knowledge, income, agriculture/livelihoods, rights, empowerment) and nutrition outcomes (child feeding, woman's diet, woman and child anthropometry). Analyses were repeated on households with ≥1 SHG member. Results: Forty percent of women were SHG members and 50% were from households with ≥1 SHG member. Only 10% of women in NI blocks had heard of intervention content at endline. Knowledge improved in both NI and STD groups. There was a positive NI impact on knowledge of timely introduction of animal-sourced foods to children ( P < 0.05) but not on other intermediate outcomes. No impacts were observed for anthropometry or diet indicators except child animal-source food consumption ( P < 0.01). In households with ≥1 SHG member, there was a positive NI impact on child unhealthy food consumption ( P < 0.05). Conclusions: Limited impacts could be due to limited exposure or skills of volunteers, and a concurrent national nutrition campaign. Our findings add to a growing literature on SHG-based BCC interventions and the conditions necessary for their success. Abstract : Community-level impacts of a volunteer-led behavior change intervention delivered through women's self-help groups in 5 Indian states on nutrition outcomes in mothers and their young children were investigated.